Business Feasibility Study of the Indonesia-China High-Speed Rail Project - Yoeyong Rahsel; Andino Maseleno (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The Indonesia-China High-Speed Rail Project is a strategic national infrastructure project operated by PT KCIC, a joint venture between a consortium of Indonesian state-owned enterprises (PSBI) and China Railway International. Although it promises modern connectivity with a travel time of 40 minutes, the project faces a major challenge in the form of cost overruns from the initial estimate to approximately US7.27 billion (around Rp118.37 trillion). This study aims to evaluate the business viability of a post-operational project, focusing on financial aspects (profitability), economic aspects (social impact), and an analysis of investment risks resulting from construction delays and debt burdens.